Analisis Sistem Akuntansi dan Pengendalian Internal Produk Tabungan Emas Pada PT Pegadaian (Persero) Cabang Pasar Mawar - Amel Febria Aigamas; Kamilah Sa'diah (Jurnal Buana Akuntansi, 2022)
Gold can be an alternative investment, one of which will be very profitable and safest, because the investment value does not have an impact on inflation, prices continue to increase. The price flexibility of buying and selling transactions makes people choose to invest in gold. This study aims to analyze the accounting system for opening accounts for gold savings products, accounting systems for product disbursement and closing accounts for gold savings products, and the application of internal control in the accounting system for gold savings products at PT Pegadaian (Persero) Pasar Mawar Branch. This research is descriptive with a qualitative analysis approach, with data collection methods using literature study techniques and documentation and observations (observations). This study concludes that the gold savings product uses an accounting system, namely the Pegadaian Application Support System Integrated Online (PASSION). The product disbursement accounting system is carried out with two methods of disbursing savings products in the form of gold and cash. The gold savings product account can be closed at any time without any conditions for depositing a nominal balance. The five components contained in internal control are Control Environment, Risk Assessment, Control Activities, Information and Communication, and Monitoring.